Reinforcing Green Consumption Intentions: Attitudes as a Mediator and the Role of Environmental Concerns, Lifestyles, Social Media, and Subjective Norms - Lily Purwianti; hepy Hefri Ariyanto; Kevin Winata; Liu Changbo (Universitas Bangka Belitung, 2025)
This study explores the determinants of green consumption intention, with attitude acting as a mediating variable. The examined characteristics include subjective norms, environmental concerns, healthy lifestyles, and social media engagement. We employed a quantitative methodology, collecting data from 396 participants via Google Forms and utilizing SEM-PLS for analysis. The results demonstrate that attitude functions as a vital mediating element in the association between the four elements and the inclination towards green consumption. Without attitude serving as a mediator, subjective norms, healthy lifestyles, and environmental concerns do not significantly impact green consumption intentions. These conclusions highlight the significant influence of mindset on the development of green consumer behavior. The study's recommendations, particularly the suggestion to incorporate factors such as the urge to spend for environmentally friendly products in future research, have the potential to inspire further exploration of the topic. The findings provide vital guidance, enabling governments and organizations to develop more effective policies that promote sustainable and environmentally responsible consumption.